DIALEKTIKA EKSENTRIK GIBRAN DALAM DEBAT PILPRES 2024 (SEBUAH PENDEKATAN HERMENEUTIKA JACQUES DERRIDA) - Deviana, Adella; Indah, Astrid (Sulesana: Jurnal Wawasan Keislaman, 2025)
This research examines Gibran's style of using gimmicks, unusual technical terms, and provocative gestures, which can be interpreted as a practice of deconstruction. He systematically undermines traditional binary oppositions such as